PELAKSANAAN PERATURAN KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 8 TAHUN 2012 TERKAIT DENGAN KINERJA PPAT DI KOTA YOGYAKARTA - , Kusumaning Triastina ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research of this study to determine the implementation of the Regulation of the National Land Agency of Republic of Indonesia Number 8 Year 2012 in the city of Yogyakarta and determine the effect of the implementation of the Regulation of the National Land Agency Republic of Indonesia Number 8 Year 2012 on the performance of PPAT in Yogyakarta. Empirical research with a research emphasis on field studies to obtain primary data. Furthermore, to complete data which obtained from field studies need to be supported by the research literature. The data used in this studyis primary data collected directly from the respondents and informants using a data collection tool such as interview guides were then developed and secondary data is data obtained from library materials through the study of documents. Data obtained from the results of research both field research and library research then analyzed qualitatively and written with descriptive methods. Based on the survey results of this study concluded that in the early stages of implementation of the Regulation of the National Land Agency of Republic of Indonesia Number 8 Year 2012 in the city of Yogyakarta, there are different perceptions about the provisions initials on each page of PPAT deed made and the lack of communication and understanding of executive resources related to the implementation of the regulation, so much PPAT deed registered at the Land Office of the city of Yogyakartais returned for reasons not in accordance with the provisions. Stage evaluations are less effective because there is no sanction provided related violations found in the implementation of these rules by the Office of the Special Province of Yogyakarta BPN to the PPAT in the city of Yogyakarta. Implementation of Regulation of the National Land Agency of Republic of Indonesia Number 8 Year 2012 is directly felt by the PPAT in Yogyakarta with the increasing performance, professionalism and independence in a deed PPAT and PPAT deed making process no longer requires a long time. Deed made by PPAT is authentic based on the provisions of the Civil Code implicitly, Government Regulation and Regulatory BPN RI. Implementation of these rules can not be separated from the support of the public service that has been provided by the PPAT in Yogyakarta and Yogyakarta City Land Office in the land registration process that is expected to create legal certainty, transparency and accountability of public services.